Prevalence and Perspectives of Complementary and Alternative Medicine among University Students in Atlanta, Newcastle upon Tyne, and New Delhi. (3rd May 2016) - Subramanian, Kritika; Midha, Inuka
Abstract : Objective . A cross-cultural comparative study was developed that surveyed university students in Atlanta (United States), New Delhi (India), and Newcastle upon Tyne (United Kingdom) to understand the prevalence and perspectives of CAM in three urban societies with different healthcare systems. Design . Surveys were sent to students in the three aforementioned cities. Survey distribution occurred over 6 months from May to November 2015. A total of 314 surveys were received. Results . Dietary and vitamin supplements had the highest prevalence collectively (n = 203 ), followed by meditation, yoga, and massage. Commentary analysis showed the importance of science and evidence in justifying CAM practice. Conclusions . Matching the most prevalent practices with their designated NCCAM categories suggested that the students were attracted to biologically based, body-based, and mind-body practices as the central themes of attraction. Selected and prevalent CAM practices suggested the students' desire to maintain physical and mental fitness. Access to healthcare may have influence on the prevalence of CAM. Indian students were more likely to view CAM as a viable alternative to conventional medicine.